Faktor – faktor sosiodemografi yang mempengaruhi terjadinya kehilangan gigi pada lansia di Desa Penatahan Penebel Tabanan - Ni Kadek Dian Candra Dewi; Putu Lestari Sudirman; I Md Ady Wirawan (School of Dentistry Faculty of Medicine Udayana University, 2018)
Background: Edentulous is a condition when the tooth is apart from its socket, which can be caused by caries, periodontal disease, trauma, and systemic disease history. Aim: The purpose of this study is to know the prevalence of tooth loss and to know sociodemographic that affecting the loss of tooth on elderly in Penatahan village. Methods: The design of this study is cross-sectional analytic. Samples of this study are elderly in Penatahan village, Tabanan aged 45-74 years. The sampling technique of this study is using total sampling of 99 people were given a questionnaire.Results: Based on the result of the bivariate analysis there were 78 (78.8%) of people who have lost of the teeth. The incidence of tooth loss by the age of the respondents has a meaningful statistical test (<0.001) with prevalence ratio (PR) CI (Confidence Interval) 95% is 0,554 (0,407-0,752), based on the incidence of tooth loss with menopause status of the respondents has a meaningful statistical test (<0.001) with prevalence ratio (PR) CI (Confidence Interval) 95% is 2.450 (1.202-4.996). Based on the result of the multivariate analysis between the variables of age, menopause status, income and occupation, factor that affecting the loss of tooth is menopause status with OR (odds ratio) CI (confidence interval) 95% is 0.16 (0,02-0,94) with a value p = 0,043. Conclusions: The conclusion of this study is that the incidences of tooth loss related with the age and menopausal status, while occupation and income has not.